(untitled) (Baghdad Science Journal, 2015)
In the hybrid coolingsolar systems , a solar collectoris used to convertsolar energy intoheat sourcein order to super heat therefrigerant leave thecompressor,andthisprocess helpsin the transformation ofrefrigerant state from gaseous statetothe liquid statein upper two-thirdsof thecondenserinstead of the lower two-thirdssuchas in thetraditional air-conditioning systems and this willreduce theenergyneeded torun the process ofcooling.In this research two hybrid air-conditioning system with an evacuated tube solar collector were used, therefrigerant was R22 and the capacity was 2 tons each.The tilt angle of the evacuated tube solar collector was changed and the solar collector fluid was replaced into oil instead of water.A comparison wasin the amount ofcurrentconsumptionof the two systems at the same operating conditions.The currentconsumptionof the hybrid coolingsystemwith the changed tilt angle and replaced fluid wasless thantheunchanged oneby(38% - 58%), meaning that there was a current consumption saving as a result of tubes tilt angle and solar collector fluid changing.